First record of Crenicichla semifasciata (Heckel, 1840) (Teleostei: Cichlidae) in the upper Rio Paraná basin, Brazil - Roa-Fuentes, Camilo A. [UNESP]; Zeni, Jaquelini O. [UNESP]; Varella, Henrique R.; Langeani, Francisco [UNESP]; Molina, Mariana C. [UNESP] (Pensoft Publishers, 2015)
Crenicichla semifasciata was described from the Rio Paraguai in Caiçara (near Cáceres, Mato Grosso, Brazil) and has been reported in the Rio Paraguai and lower portion of the Rio Paraná downstream of the Itaipu hydroelectric dam, but considered absent in the upper Rio Paraná and in the Rio Uruguai basin. In this paper, we document the first record of C. semifasciata in a first order stream of the Ribeirão Buritis, tributary of the Rio São José dos Dourados, upper Rio Paraná basin.
Keywords: Fish introduction; La plata basin; Non-native species; Rio são josé dos dourados